Chemical composition of oat (Avena sativa L.) crop components, Chihuahua variety - Mendoza-Pedroza, Sergio Iban; Sosa-Montes, Eliseo; Rodríguez-Ortega, Leodan Tadeo; Vasquez-Gomez, Isabel Lily; Ramírez-Bribiesca, Jacinto Efrén; Hernández-Guzmán, Filogonio Jesús (Ecosistemas y Recursos Agropecuarios, 2021)
For its importance as a partially characterized strategic winter crop, the forage oat Chihuahua variety was studied. In leaf, stem, weed, panicle, and whole plant, neutral detergent fiber (NDF), acid detergent fiber (ADF), crude lignin (CL), ashes (Ash), crude protein (CP), and crude fat (CF) were determined (g 100 g-1), and their corresponding yields (kg ha-1) were assessed. The CP in leaf, stem, weed, and the whole plant decreased (p < 0.05) while NDF, ADF, and CL contents increased (p < 0.05) as cutting age progressed. The CF content increased with age in leaf and panicle (p < 0.05), but no changes were observed in stem and weed (p > 0.05). In panicle, the content of NDF strongly decreased, 21.6% (p < 0.05), and that of CP decreased slightly, 1.0% (p < 0.05), while those of CL and CF increased (p < 0.05) as age progressed. A maximum CP yield was detected in leaf and weeds at 75 days of age while in stem the maximum CP yield occurred at 90 days. For the oat forage, Chihuahua variety does not contain so much fiber and in order that the content and yield of protein are not so low, it is suggested to harvest this plant between 75 and 90 days of age.